La intuición, el fenómeno y sus formas : estética trascendental y certeza sensible - (:unkn) unknown (Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Filosofía, 2001)
In this work we try to show the notable presence of Kantian developments in the dialectic of Sence Certainty of Hegel's Phenomenology of Mind. In particular, we sustain that the internal moments of this dialectic correspond to three characteristics of Kantian forms of sensibility : space and time as forms of intuition, forms of appearance and as pure intuitions.
42 ref.
Fil: Pringe, Hernán. Universidad de Buenos Aires. Facultad de Filosofía y Letras; Argentina
Fil: Pringe, Hernán. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina
Keywords: FILOSOFÍA; CONCIENCIA; COMPARACIÓN; HEGEL, GEORG WILHELM FREDERIK; FENOMENOLOGÍA DEL ESPÍRITU / HEGEL, G. W. F.; KANT, IMMANUEL; CRÍTICA DE LA RAZÓN PURA / I. KANT